Les sociétés rurales européennes ont-elles accepté les politiques publiques paysagères ? - Pierre Donadieu (Projets de Paysage)
This text analyzes the consequences of landscape public policies on rural societies in Europe. They face the risk to be divided in three categories of relations with the farming and wooded spaces : encouraging cultivation and gardening of local services for practices of residential, leisure and tourism ; encouraging the maintaining of agro-industries in intensive farming regions ; or in the two precedent cases, by involving values of sustainable development, implementing land project in the perspective of a localized and sustainable auto-development. According to their productions and their projects, the farmers will stand in two very different situations. Either they will resist to the public sustainable landscape project by running away from it (relocation outside Europe or far from the cities) ; or they will integrate a local asset of sustainable development in their trade activities, with the assistance of the farm territories and lands inhabitants. The local authorities will be expected to find governing rules to manage and control these evolutions.